[18F]PSMA-1007 PET/CT-based radiomics may help enhance the interpretation of bone focal uptakes in hormone-sensitive prostate cancer patients. - Bauckneht, Matteo; Pasini, Giovanni; Di Raimondo, Tania; Russo, Giorgio; Raffa, Stefano; Donegani, Maria Isabella; Dubois, Daniela; Peñuela, Leonardo; Sofia, Luca; Celesti, Greta; Bini, Fabiano; Marinozzi, Franco; et al. (European Journal of Nuclear Medicine & Molecular Imaging, 2025)
Purpose: We hypothesised that applying radiomics to [18F]PSMA-1007 PET/CT images could help distinguish Unspecific Bone Uptakes (UBUs) from bone metastases in prostate cancer (PCa) patients. We compared the performance of radiomic features to human visual interpretation. Materials and methods: We retrospectively analysed 102 hormone-sensitive PCa patients who underwent [18F]PSMA-1007 PET/CT and exhibited at least one focal bone uptake with known clinical follow-up (reference standard). Using matRadiomics, we extracted features from PET and CT images of each bone uptake and identified the best predictor model for bone metastases using a machine-learning approach to generate a radiomic score. Blinded PET readers with low (n = 2) and high (n = 2) experience rated each bone uptake as either UBU or bone metastasis. The same readers performed a second read three months later, with access to the radiomic score. Results: Of the 178 [18F]PSMA-1007 bone uptakes, 74 (41.5%) were classified as PCa metastases by the reference standard. A radiomic model combining PET and CT features achieved an accuracy of 84.69%, though it did not surpass expert PET readers in either round. Less-experienced readers had significantly lower diagnostic accuracy at baseline (p < 0.05) but improved with the addition of radiomic scores (p < 0.05 compared to the first round). Conclusion: Radiomics might help to differentiate bone metastases from UBUs. While it did not exceed expert visual assessments, radiomics has the potential to enhance the diagnostic accuracy of less-experienced readers in evaluating [18F]PSMA-1007 PET/CT bone uptakes.